The Role of Mega-Sport Development in Projects of Urban Renewal − Investigating the "Lansdowne Partnership Plan" in Ottawa - DuPlessis, Joel (Université d'Ottawa | University of Ottawa, 2014)
Cities are attempting to benefit from of the globalized economy by branding themselves as locations for tourism, investment and consumption. Consequently, cities are planning and executing urban expansion projects with a focus on image and marketability—tactics that directly impact how cities are perceived by global and domestic onlookers. This research paper reports on the City of Ottawa's decision to partner with the Ottawa Sports and Entertainments Group (OSEG) in the redevelopment of Lansdowne Park. Specifically, this paper examines local opposition to the redevelopment and motivations behind the City's decision to partner with a private interest group. Core concepts and ideas of the field of urban communication are explored in this research. The findings indicate that the City is taking on characteristics of the entrepreneurial city; rebuilding Lansdowne Park with a focus on image and marketability in order to sell the City as a location for investment, tourism and entertainment.